The protective performance of different types of motorcycle helmets in terms of HIC and BRIC - N. Q., Radzuan; Mohd Hasnun Ariff, Hassan; Mohd Nadzeri, Omar; Khairil Anwar, Abu Kassim (Springer Nature, 2024)
This research evaluates the protective performance of full-face, open-face, and half-coverage motorcycle helmets by taking the head injury criterion (HIC) and brain injury criterion (BrIC) as performance indicators. A pendulum test rig was developed to produce a 5.58 ± 0.29 m/s impact speed. The researchers gave a head impact with or without a helmet to an anthropomorphic test device (ATD) head and neck called Hybrid III at its frontal, rear, and side areas. The Hybrid III had an installed Shimmer 200 g IMU sensor in its skull. The raw data output was linear and rotational velocities recorded using ConsensysPro software version 1.6.0. The linear velocity data are then processed by MATLAB® 2016b software because its raw data are uncalibrated. Calibrated linear and rotational velocities were then used to calculate HIC and BrIC. The research can determine no definite best helmet type through the crash impact experiment; as a result it shows the inconsistency of HIC score among three different types of helmets at each impact location. Furthermore, the research found that the helmet type did not provide significant protection towards rotational impact. It is worth mentioning that side impact may cause the highest injury severity due to rotational motion.